Extracting keywords from meeting documents - Chua, Calson (Philippine computing journal)
Information plays an important role for management to make sound decision in an organization. As organization keeps documents in electronic format, it appears that aside from the possible, well-organised folders in a disk and well-meaning filenames given to documents, searching documents based on contents is difficult. In addition, most if not all document search requires the user to recall exact phrases in the document for search and retrieval. In an organization where administrators changes over time, decisions, recommendations, suggestions and other important things that were recorded formally in a document may remain unknown to new administrators. New administrators may have to exert pro-active efforts to retrieve previous decisions before making a new one, due to possible contradiction or repetition. As the volume of document increases, search and retrieval become tedious and difficult. This study presented an approach to parse and analyse meeting documents to extract keywords in preparation for indexing and clustering..